2015
DOI: 10.1371/journal.pone.0127244
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Sulforaphane-Rich Broccoli Sprout Extracts during Juvenile and Adolescence Can Prevent Phencyclidine-Induced Cognitive Deficits at Adulthood

Abstract: Oxidative stress and inflammation play a role in cognitive impairment, which is a core symptom of schizophrenia. Furthermore, a hallmark of the pathophysiology of this disease is the dysfunction of cortical inhibitory γ-aminobutyric acid (GABA) neurons expressing parvalbumin (PV), which is also involved in cognitive impairment. Sulforaphane (SFN), an isothiocyanate derived from broccoli, is a potent activator of the transcription factor Nrf2, which plays a central role in the inducible expressions of many cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 61 publications
3
62
0
Order By: Relevance
“…Subsequently, we also reported that dietary intake of SFN-rich broccoli sprout extracts during juvenile and adolescence can prevent PCP-induced cognitive deficits and loss of parvalbumin (PV) immunoreactivity in the prefrontal cortex (PFC) at adulthood [30,31]. These finding suggest that SFN could be a potential prophylactic natural compound for neuropsychiatric diseases [29][30][31].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Subsequently, we also reported that dietary intake of SFN-rich broccoli sprout extracts during juvenile and adolescence can prevent PCP-induced cognitive deficits and loss of parvalbumin (PV) immunoreactivity in the prefrontal cortex (PFC) at adulthood [30,31]. These finding suggest that SFN could be a potential prophylactic natural compound for neuropsychiatric diseases [29][30][31].…”
Section: Introductionmentioning
confidence: 91%
“…LPS and SFN were administered intraperitoneally (ip) into mice. The doses of LPS (0.5 mg/kg) and SFN were selected by previous reports [10][11][12][13][29][30][31]]. …”
Section: Drug Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous study reported that dietary intake of sulforaphane-rich broccoli sprout extracts during juvenile and adolescence prevented phencyclidine-induced cognitive deficits [16]. That indicated the pharmacological activity of SFN in recovery of memory impairment.…”
Section: Discussionmentioning
confidence: 81%